Trade cost and its impact on agri-food trade growth among China, EU and ASEAN : in partial fulfilment of the requirement for the degree of Master of AgriCommerce, Massey University, Palmerstone North, New Zealand - Fang, Ling (Massey University, 2017)
Trade cost is broadly defined to include all costs incurred in getting a good to a final user other than the marginal cost of producing the good itself. According to Anderson and van Wincoop (2003), a rough estimate of the tax equivalent trade costs for industrialized countries is 170 percent. While compared to industrial products, agricultural goods suffer more from trade cost due to its low value to volume ratio and perishable characteristic as well as high protection in both developed and developing economies. By using the trade cost index developed by Dennis Novy (2013), this study examines the trade costs and its relationship with trade growth among China, EU, and ASEAN in agricultural sector. The results indicate that first, although the bilateral agricultural trade among these three economies have been growing steadily over last fifteen years, their trade costs are still high. In particular, the average trade cost between China and EU is about 633 percent tax equivalent. Secondly, economic growth is still the key driver of trade expansion. The contribution of trade cost reduction varies among trading pairs. In the case of China & ASEAN and EU & ASEAN, its impact is limited. But, in the case of China and EU, it contributes over half of the overall trade growth. Combined with the fact that China now has converted from a net exporter to a net importer of EU’s agricultural products, a further trade liberalization between these two could possibly increase bilateral trade significantly. Thirdly, the reduction of multilateral trade barriers diverts large amount of bilateral trade. The trade diversion effect of regional trade agreement is one possible reason. Finally, compared to distance, which is a static number, the trade cost index has a better explanatory power. It is time sensitive, more comprehensive, and not hard to compute.
Keywords: Food industry and trade; International trade; Produce trade; China; European Union; Asia, Southeastern; ASEAN; Research Subject Categories::SOCIAL SCIENCES::Business and economics::Economics